2013
DOI: 10.1111/cea.12034
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors are associated with hypersensitivity reactions to drugs in hospitalized patients: a nested case‐control in a retrospective cohort study

Abstract: In hospitalized patients, the use of proton pump inhibitors was associated with a significant increase risk of drug hypersensitivity reactions along with a personal history of drug allergies and long hospitalization time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…The PPIs being potent inhibitors of gastric acid secretion have been extensively studied in preventing aspirininduced GI complications. Recently, we are facing the side effects of long-term PPI therapy, such as Clostridium difficile colitis, community-acquired pneumonia, osteoporosis, iron and vitamin deficiencies, as well as the increase of food allergies [45][46][47][48][49]. The interaction caused by PPIs on the cytochrome enzymes hazard appropriate drug actions of clopidogrel, vitamin K antagonists, and benzodiazepines [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The PPIs being potent inhibitors of gastric acid secretion have been extensively studied in preventing aspirininduced GI complications. Recently, we are facing the side effects of long-term PPI therapy, such as Clostridium difficile colitis, community-acquired pneumonia, osteoporosis, iron and vitamin deficiencies, as well as the increase of food allergies [45][46][47][48][49]. The interaction caused by PPIs on the cytochrome enzymes hazard appropriate drug actions of clopidogrel, vitamin K antagonists, and benzodiazepines [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In 161 hospitalized patients, after controlling for confounders, the odds ratio of confirmed drug hypersensitivity was 4.35 (95% CI 2.0-9.45) in those receiving a proton pump inhibitor compared with matched controls. A personal history of drug allergy and a long hospitalization time were also significant risk factors [34]. …”
Section: Triggers and Mechanismsmentioning
confidence: 99%
“…Some studies which evaluated the risk factors for severe reactions in drug-induced anaphylaxis reported that comorbidities involving chronic lung diseases or cardiac diseases and drugs used simultaneously such as β-blockers, ACEI/ARBs, or PPIs increased the risk of severe anaphylaxis, but others did not observe such a relationship [39, 55, 56]. We observed that anaphylaxis was more common in hypersensitive patients and the patients who used ACEI/ARBs in the univariate analysis.…”
Section: Discussionmentioning
confidence: 51%